Exploring the link between maternal attachment-related anxiety and avoidance and mindful parenting: The mediating role of self-compassion - Moreira, Helena (2016)
Mindful parenting has been described as a set of parental practices or skills that seek to enhance moment-to-moment awareness in the parent-child relationship. Although it has been suggested that adopting a mindful approach in parenting may foster positive parent-child relationships and promote the psychological functioning of children and parents, little is known about the factors that may be associated with this parental skill. In this study, we aimed to examine whether attachment-related anxiety and avoidance were associated with mindful parenting through self-compassion.